1990
DOI: 10.1128/mcb.10.2.859
|View full text |Cite
|
Sign up to set email alerts
|

Efficient transcription of the glycolytic gene ADH1 and three translational component genes requires the GCR1 product, which can act through TUF/GRF/RAP binding sites.

Abstract: Glycolytic gene expression in Saccharomyces cerevisiae is thought to be activated by the GCR and TUF proteins. We tested the hypothesis that GCR function is mediated by TUF/GRF/RAP binding sites (UASRPG elements). We found that UASRPG-dependent activation of a heterologous gene and transcription of ADH1, TEF1, TEF2, and RP59 were sensitive to GCR1 disruption. GCR is not required for TUF/GRF/RAP expression or in vitro DNA-binding activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 12 publications
1
32
0
Order By: Relevance
“…Not depicted in the figure are Bmh1 and Bmh2, the yeast homologues of 14-3-3 proteins, which have been shown recently to be involved in TOR signaling (Bertram et al, 1998). of many r-protein genes, as well as Gcr1, a protein required for the activity of both r-protein genes as well as genes involved in glycolysis (Santangelo and Tornow, 1990;Tornow et al, 1993). In support of possible involvement of Gcr1 in TOR signaling, we have observed that rapamycin also severely inhibits expression of several glycolytic genes, including ADH1, ENO1, and PGK1 (our unpublished results).…”
Section: Discussionmentioning
confidence: 99%
“…Not depicted in the figure are Bmh1 and Bmh2, the yeast homologues of 14-3-3 proteins, which have been shown recently to be involved in TOR signaling (Bertram et al, 1998). of many r-protein genes, as well as Gcr1, a protein required for the activity of both r-protein genes as well as genes involved in glycolysis (Santangelo and Tornow, 1990;Tornow et al, 1993). In support of possible involvement of Gcr1 in TOR signaling, we have observed that rapamycin also severely inhibits expression of several glycolytic genes, including ADH1, ENO1, and PGK1 (our unpublished results).…”
Section: Discussionmentioning
confidence: 99%
“…Not surprisingly, these are the genes most abundantly transcribed by RNA polymerase II in S. cerevisiae cultures growing rapidly on glucose; 26 of the 30 most highly expressed transcription units are in one of these two groups (392). Overall the Rap1 activation mechanism(s) accounts for 60 to 75% of RNA polymerase II transcription in rapidly growing cells (324,410).…”
Section: The Cell Cycle Connectionmentioning
confidence: 99%
“…Transcriptional activation by Rap1 was shown long ago to exhibit sensitivity to disruption of GCR1 (81,324,435). Genome-wide analysis has now demonstrated for the entire genome that genes with a Rap1 binding site in their promoter are also Gcr1 target genes (81,211,324,375,435).…”
Section: Transcriptional Induction Of Glycolytic and Ribosomal Proteimentioning
confidence: 99%
“…At the UAS of the glycolytic genes ENO1, TPI, and PYK1, Rap1p functions to promote the binding of Gcr1p, a protein that interacts with DNA only very weakly on its own (2,15,52). This could be achieved via a direct protein-protein interaction or by some effect of Rap1p on the surrounding DNA (44,51). There may also be some redundancy of function within the Nand C-terminal domains of Rap1p because it can promote DNA binding by Gcr1p in vitro as long as the DNA binding domain plus either the N terminus or the C terminus is present (33).…”
mentioning
confidence: 99%